2001
DOI: 10.1017/s019594170007274x
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Nosocomial Sepsis and Pneumonia in a Newborn Intensive Care Unit by Multiresistant Extended-Spectrum β-Lactamase-ProducingKlebsiella pneumoniaeHigh Impact on Mortality

Abstract: We describe a case-control study of a small outbreak of nosocomial sepsis and pneumonia with high mortality due to clonal dissemination of a multiresistant Klebsiella pneumoniae in the neonatal intensive care unit of a Mexican institution. Our study helped to change nosocomial infection control policy in this hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Contrary to this, a study from Mexico showed a significantly lower proportion of trained nurses caring for critically ill patients during epidemic periods of ESBL-producing K. pneumoniae. 14 In our unit, as mentioned, there were more category 4-5 patients before and during outbreaks.…”
Section: Discussionmentioning
confidence: 56%
“…Contrary to this, a study from Mexico showed a significantly lower proportion of trained nurses caring for critically ill patients during epidemic periods of ESBL-producing K. pneumoniae. 14 In our unit, as mentioned, there were more category 4-5 patients before and during outbreaks.…”
Section: Discussionmentioning
confidence: 56%
“…K. pneumoniae can cause severe morbidity and mortality especially among the newborn (Bingen, 1993;Casolari et al, 2005;Coovadia et al, 1992). In recent years, K. pneumoniae have frequently been reported as the cause of outbreaks involving newborn infants in neonatal intensive care units (Fangyou et al, 2009;Randrianirina et al, 2009;Jerassy et al, 2006;Casolari et al, 2005;Wachino, Doi, & Yamane, 2004;Gastmeier, Groneberg, & Weist, 2003;Lebessi et al, 2002;Martinez-Aguilar et al, 2001;Macrae et al, 2001;Roilides et al, 2000;van der Zwet et al, 1999;Al-Rabea et al, 1998;Villari, Iacuzio, Torre, & Scarcella, 1998;Banerjee et al, 1993;Reish, Ashkenazi, Naor, Samra, & Merlob, 1993;Arredondo-Garcia, Diaz-Ramos, Solorzano-Santos, Sosa-Gonzalez, & Beltran-Zuniga, 1992;Denny, St.-John, Lewis, & Daniel, 1986;Donowitz, Marsik, Fisher, & Wenzel, 1981;Hill, Hunt, & Matsen, 1974;Mayhall et al, 1980;Saravolatz, Arking, Pohlod, Fisher, & Borer, 1984;Sveningsen, Bekassy, Christensen, & Kamme, 1984). K. pneumoniae have also been found in powdered infant formula (Carneiro, Silva, Merquior, & Queiroz, 2003;Muytjens, RoelofsWillemse, & Jaspar, 1988).…”
Section: Introductionmentioning
confidence: 99%